The 60th Brazilian Ceramic Conference : selected, peer reviewed papers from the 60th Brazilian Ceramic Conference, May 15-18, 2016, Sao Paulo, Brazil - Ribeiro, Sebastiän (Materials science forum, 2018)
This book based on the results of the 60th Brazilian Ceramic Conference (CBC 60, Sao Paulo, Brazil, from May 15th to the 18st, 2016). The collection reflects the latest achievements in the researching of the properties of the different ceramic materials and highlights results of use the ceramics materials in the various spheres of the modern manufacturing. We hope that presented articles will be interesting and useful for many researchers and engineers. Ceramics, Clay, Nanocomposites, Glass-Ceramics, Semiconductor Oxides, Ferrites, Ceramics Processing, Microstructural and Mechanical Properties, Ceramic Coating Materials Science.